Incidence of Ostomy Site Incisional Hernias after Stoma Closure. Issue 12 (December 2015) - Sharp, Stephen P.; Francis, Jacquelyn K.; Valerian, Brian T.; Canete, Jonathan J.; Chismark, A. David; Lee, Edward C.
This study sought to evaluate the incidence of ostomy site incisional hernias after stoma reversal at a single institution. This is a retrospective analysis from 2001 to 2011 evaluating the following demographics: age, gender, indication for stoma, urgent versus elective operation, time to closure, total follow-up time, the incidence of and reoperation for stoma incisional hernia, diabetes, postoperative wound infection, smoking status within six months of surgery, body mass index, and any immunosuppressive medications. A total of 365 patients were evaluated. The median follow-up time was 30 months. The clinical hernia rate was 19 percent. Significant risk factors for hernia development were age, diabetes, end colostomies, loop colostomies, body mass index >30, and undergoing an urgent operation. The median time to clinical hernia detection was 32 months. Sixty-four percent of patients required surgical repair of their stoma incisional hernia. A significant number of patients undergoing stoma closure developed an incisional hernia at the prior stoma site with the majority requiring definitive repair. These hernias are a late complication after stoma closure and likely why they are under-reported in the literature.